BUDIDAYA TANAMAN HERBAL (APOTIK HIDUP) SEBAGAI SALAH SATU BENTUK KEPEDULIAN MASYARAKAT UNTUK KESEHATAN Herbal Plant Cultivation (Living Pharmacy) As A Form Of Community Concern For Health - Rahmi Sari, joni Rianto (JURNAL BIMA, 2025)
This community service aims to increase community awareness and skills in cultivating herbal plants as an independent effort to maintain family health. This program was implemented in Sejahtera Village, Makmur District, involving 50 heads of families as participants. Implementation methods include counseling, training in cultivation practices, and ongoing assistance. Herbal plants cultivated include ginger, turmeric, galangal, lemongrass, mint leaves, and bitter. The results of the activity showed an increase in participants' knowledge by 85% and 90% of participants succeeded in implementing herbal plant cultivation in their home gardens. This program contributes to increasing family health resilience and reducing dependence on chemical drugs.